Responsible Dissemination in Sexual Orientation Research: The Case of the AI "Gaydar". Issue 5 (30th December 2022) - De Block, Andreas; Conix, Stijn
Abstract: A recent controversy about neural networks allegedly capable of detecting a person's sexual orientation raises the question of whether all research on homosexuality should be permitted. This paper considers two arguments for limits to such research, and concludes that there are good reasons to limit at least the dissemination of applied research on the etiology of homosexuality. The paper then briefly sketches how this could work, and looks at three objections against these limitations.